Educational Resilience of Urban Squatter Children in Kathmandu - Rai, Indra Mani; Luitel, Bal Chandra; Gautam, Suresh; Pant, Binod Prasad; Gautam, Santosh (Journal of Education and Research, 2016)
Squatters are the illegal tenants residing in public lands as immigrants due to livelihood collapse in their origins. They have been denied of public resources and urban facilities because of their identity crisis leading to a vicious circle of poverty with impoverished livelihood creating multifaceted adversities of learning for their children. In this context, this paper, based on a cyclical mixed method research design under transformative research approach, has explored the learning adversities faced by the squatter children of Kathmandu Metropolitan city, their protective and promotive strategies to cope with adversities and life-skills as learning outcomes. Squatter children are struggling against the backdrop of exposure to unhygienic settlements with low health conditions, poverty with impoverished livelihood, and illiteracy of parents, poor homely environment, and dysfunctional families. Despite such adversities, they were able to continue school education with the support of their teachers, peers, parents and families. The research study finds stronger family and community assets of the students. These assets are helpful for building educational resilience of the squatter children.